PENERAPAN MODEL PEMBELAJARAN PjBL DALAM PEMBELAJARAN SENI KARYA UNTUK MENINGKATKAN KREATIFITAS SISWA KELAS IV UPTD SDI BAKUNASE II - Seran, Maria; Koro, Maxel; Benu, Adama; Ndolu, Mardi (SENTRI: Jurnal Riset Ilmiah, 2024)
This research aims to increase creativity using the Project Based Learning model in grade IV of SDI Bakunase 2 Kupang City. This type of research is Classroom Action Research (PTK) with the following stages: planning, implementation, observation, and reflection. The subjects in this study are 18 students in grade IV of SDI Bakunase 2 Kupang City consisting of 9 female students and 9 male students. Data collection is carried out by test, observation, and documentation techniques. This data is analyzed using quantitative data analysis techniques. The results of the first cycle test assessment there were 14 students (78%) who completed while the other 4 students (22%) had not been completed. In the second cycle, 16 students (89%) completed and 2 students (11%) did not complete. The increase in students’ creativity can be seen from the increase in the average score of accuracy, concentration, and clarity. Therefore, it can be concluded that there is a significant influence on efforts to increase creativity using the Project Based Learning model.